Research progress of pain catastrophizing in patients after surgical treatment of lung cancer (肺癌术后患者疼痛灾难化的研究进展) - BIAN Guanjun (边冠军); ZHANG Chunmei (张春梅); LIU Lifeng (刘丽峰) (中西医结合护理)
This paper reviewed current research status of pain catastrophizing in patients with lung cancer after surgery, and summarized the concept, theoretical basis, assessment tools, epidemiological characteristics, influencing factors and management strategies of pain catastrophizing, in order to provide theoretical support for medical personnel to develop targeted and effective pain management strategies. (综述肺癌术后患者疼痛灾难化的研究现状, 归纳疼痛灾难化的概念、理论基础、评估工具、流行病学特征、影响因素及管理策略, 旨在为医务人员制定针对性、有效性的疼痛管理策略提供理论支持。)